Air cathode catalyst for zinc-air battery, method for preparing the same, air cathode comprising the same, and zinc-air battery
By coating a polymer active layer with an iron macrocycle compound on a carbon nanotube support, the conductivity and charge transfer resistance of zinc-air batteries are enhanced, addressing the limitations of manganese dioxide-based catalysts and improving battery performance.
Patent Information
- Application Number
- KR1020260036781
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-02-27
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-02-27
AI Technical Summary
Zinc-air batteries face limitations in power density, energy efficiency, and specific capacity due to low intrinsic electrical conductivity of manganese dioxide-based catalysts, which lead to electron transfer bottlenecks, structural changes, and two-electron peroxide generation, hindering high power output and long lifespan operation.
A polymer active layer containing an iron (Fe) macrocycle compound is coated on a carbon nanotube support to enhance electronic conductivity and reduce charge transfer resistance, forming a π-conjugated polymer chain for improved electron delocalization and active site stability.
The solution improves the output, energy efficiency, and specific capacity of zinc-air batteries by enhancing electronic conductivity and reducing charge transfer resistance, ensuring stable performance under high current density conditions.
Smart Images

Figure 112026024612838-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an air electrode catalyst for a zinc-air battery, a method for manufacturing the same, an air electrode comprising the air electrode catalyst, and a zinc-air battery. More specifically, the invention relates to an air electrode catalyst for a zinc-air battery capable of improving the output, energy efficiency, and specific capacity of a zinc-air battery by coating a polymer active layer containing an iron (Fe) macrocycle compound on a carbon nanotube support to enhance electronic conductivity and reduce charge transfer resistance (R_ct), and to an air electrode comprising the same and a zinc-air battery.
[0002] In addition, the invention relates to a method for manufacturing an air electrode catalyst capable of precisely coating a polymer active layer containing an iron (Fe) macrocycle compound onto a carbon nanotube support with high density and high dispersion. Background Technology
[0004] Zinc-air batteries have high energy density characteristics compared to lead-acid batteries, nickel-cadmium batteries, nickel-hydrogen batteries, and lithium-ion batteries. In addition to having superior safety characteristics compared to the instability caused by lithium in lithium batteries, they are attracting significant attention as alternative energy storage devices for various electronic devices because they have the advantages of low manufacturing costs and being pollution-free batteries that do not emit pollutants, as they use zinc, one of the most abundant metals on Earth.
[0005] These zinc-air batteries utilize a stable zinc-based anode and an aqueous electrolyte, and since the discharge reaction occurs by using ambient air as fuel for the cathode, the risk of short-circuit heat, ignition, or explosion caused by external shock is significantly low. As such, they are suitable as power sources for portable electronic devices, and research and development are currently underway to utilize them as power sources for military communication equipment and high-capacity charging devices.
[0006] Regarding air electrode catalysts, a key factor determining the performance of zinc-air batteries, manganese dioxide (MnO2)-based catalysts are currently widely used in the commercialization stage due to their low-cost advantage. However, manganese dioxide has low intrinsic electrical conductivity, making it prone to electron transfer bottlenecks within the electrode; furthermore, there are issues with structural changes or dissolution, particularly under alkaline electrolyte and high current density conditions. Additionally, instead of an efficient four-electron reaction, two-electron (e) - Peroxide generation is induced through the pathway, leading to loss of catalytic active sites and aging of the electrode structure during long-term operation, which acts as a critical limitation hindering high power output and long lifespan operation of the battery.
[0007] Accordingly, there is a need to develop next-generation high-activity air electrode catalyst technology capable of simultaneously improving the power density, energy efficiency, and specific capacity of zinc-air batteries by enhancing electron conductivity within the electrode and reducing charge transfer resistance (R_ct). Prior art literature
[0009] Korean Registered Patent Publication No. 10-1424741 (July 23, 2014) Korean Published Patent Publication No. 10-2021-0045030 (April 26, 2024) The problem to be solved
[0010] Accordingly, the technical problem of the present invention is conceived from this point. The present invention relates to an air electrode catalyst for a zinc-air battery, a method for manufacturing the same, an air electrode including the air electrode catalyst, and a zinc-air battery. More specifically, by coating a polymer active layer containing an iron (Fe) macrocycle compound on a carbon nanotube support, the present invention provides an air electrode catalyst for a zinc-air battery capable of improving the output, energy efficiency, and specific capacity of the zinc-air battery by enhancing electronic conductivity and reducing charge transfer resistance (R_ct), and an air electrode including the same and a zinc-air battery.
[0011] In addition, a method for manufacturing an air electrode catalyst is provided, which can precisely coat a polymer active layer containing an iron (Fe) macrocycle compound onto a carbon nanotube support with high density and high dispersion. means of solving the problem
[0013] According to one embodiment of the present invention, an air electrode catalyst for a zinc-air battery is provided, comprising: a conductive carbon nanotube (CNT) support; and a polymer active layer formed on the surface of the carbon nanotube support and containing an iron (Fe) macrocycle compound.
[0014] At this time, the iron (Fe) macrocycle compound includes an iron phthalocyanine (Fe-Phthalocyanine) or iron porphyrin (Fe-Porphyrin) structure, and the structure can be connected as repeating units to form a π-conjugated polymer chain.
[0015] At this time, the thickness of the polymer active layer containing the iron (Fe) macrocycle compound may be 0.5 nm.
[0016] According to another embodiment of the present invention, a method for manufacturing an air electrode catalyst for a zinc-air battery comprises the steps of: preparing a carbon nanotube support; and supporting a polymer powder on the surface of the carbon nanotube support to form a polymer active layer containing an iron (Fe) macrocycle compound on the surface of the carbon nanotube support.
[0017] At this time, the polymer powder can be formed by mixing an iron precursor and a nitrogen-containing organic ligand, dissolving the mixed iron precursor and nitrogen-containing organic ligand in an organic solvent, centrifuging the dissolved solution mixed with the iron precursor and nitrogen-containing organic ligand, and drying the solution.
[0018] At this time, when forming the polymer powder, the iron precursor and the nitrogen-containing organic ligand may be mixed in a ratio of 20 to 30 weight% of the iron precursor and 70 to 80 weight% of the nitrogen-containing organic ligand based on the total weight thereof.
[0019] At this time, the polymer active layer containing the iron (Fe) macrocycle compound is an iron precursor, and the nitrogen-containing organic ligand may be TCNB.
[0020] At this time, the step of forming a polymer active layer containing the iron (Fe) macrocycle compound comprises: a step of preparing a dispersion by dispersing the polymer powder in a polar organic solvent; and a step of mixing and stirring carbon nanotube powder in the dispersion; wherein, the polymer powder and the carbon nanotube powder may be mixed in a ratio of 15 to 20 weight% of the polymer powder and 80 to 85 weight% of the carbon nanotube powder based on their total weight.
[0021] According to another embodiment of the present invention, an air electrode of a zinc-air battery is provided, characterized by comprising: a carbon material including activated carbon and carbon black; a catalyst part including manganese dioxide (MnO2) and the air electrode catalyst; and a PTFE (Polytetrafluoroethylene) binder.
[0022] At this time, the air electrode comprises, based on 100 weight% of the total, 70 to 80 weight% of activated carbon, 1 to 2 weight% of Black Pearl, and 0.5 to 1 weight% of Super P as the carbon material, 7 to 8 weight% of manganese dioxide (MnO2) as the main catalyst of the catalyst part, and 15 to 20 weight% of PTFE (Polytetrafluoroethylene) as the binder, and may include the air electrode catalyst according to claim 1 as an additive of the catalyst part in a ratio of 4 to 6 weight parts relative to 100 weight parts of manganese dioxide (MnO2).
[0023] Meanwhile, according to another embodiment of the present invention, a zinc-air battery comprising the air electrode catalyst is provided. Effects of the invention
[0025] According to an embodiment of the present invention, by coating a polymer active layer containing an iron (Fe) macrocycle compound on a carbon nanotube support, the electronic conductivity is improved and the charge transfer resistance (R_ct) is reduced, thereby improving the output, energy efficiency, and specific capacity of a zinc-air battery.
[0026] In addition, it has the effect of enabling the precise coating of a polymer active layer containing an iron (Fe) macrocycle compound onto a carbon nanotube support with high density and high dispersion.
[0028] The effects of the present invention are not limited to those mentioned above, and other unmentioned effects will be clearly understood by those skilled in the art from the description in the claims. Brief explanation of the drawing
[0030] The summary described above, as well as the detailed description of the preferred embodiments of the present application described below, will be better understood when read in conjunction with the accompanying drawings. Preferred embodiments are illustrated in the drawings for the purpose of illustrating the invention. However, it should be understood that the present application is not limited to the exact arrangements and means illustrated. Figure 1 is a schematic diagram showing the structural formula of a polymer containing an iron (Fe) macrocycle compound. Figure 2 is a reference diagram illustrating the effect that an air electrode catalyst coated with a polymer active layer containing an iron (Fe) macrocycle compound according to the present invention has superior electron conductivity and charge transfer resistance compared to an air electrode catalyst coated with a monomer active layer containing an iron (Fe) macrocycle compound. Figure 3 is a reference diagram for explaining a structure in which a polymer containing an iron (Fe) macrocycle compound is continuously coated on the surface of a CNT support. Figure 4 is a reference diagram to explain that the Fe signal is evenly distributed across the entire coating layer of a polymer containing an iron (Fe) macrocycle compound formed on the surface of a CNT support. Figures 5 and 6 are reference diagrams for explaining the performance characteristics of a zinc-air battery according to the content of an air electrode catalyst coated with a polymer active layer containing an iron (Fe) macrocycle compound. Specific details for implementing the invention
[0031] Embodiments of the present invention will be described in detail below with reference to the attached drawings. However, it will be readily apparent to those skilled in the art that the attached drawings are provided merely to facilitate the disclosure of the content of the present invention, and that the scope of the present invention is not limited to the scope of the attached drawings.
[0032] Furthermore, in describing the embodiments of the present invention, it is stated in advance that components having the same function are not substantially identical to the components of the prior art, even though the same names and symbols are used.
[0033] Furthermore, the terms used in this application are used merely to describe specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this application, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0035] Hereinafter, an air electrode catalyst for a zinc-air battery according to the present invention, a method for manufacturing the same, an air electrode including the air electrode catalyst, and a zinc-air battery will be described in detail with reference to the attached drawings. In describing with reference to the attached drawings, identical or corresponding components are given the same reference numerals, and redundant descriptions thereof will be omitted.
[0037] Zinc-air batteries are eco-friendly and economical batteries primarily used in electric vehicles, portable electronic devices, and energy storage systems. They generate electricity using oxygen from the air and consist of a zinc electrode (negative electrode) and an air electrode (positive electrode).
[0038] Among these, the air electrode receives oxygen through a multilayer structure including a gas diffusion layer (GDL), a catalyst layer, a current collector, and a binder to perform an electrochemical reaction.
[0039] The air electrode catalyst of a zinc-air battery according to the present invention comprises a carbon nanotube (CNT) support (hereinafter referred to as 'CNT support') and a polymer active layer containing an iron (Fe) macrocycle compound, thereby improving electronic conductivity and reducing charge transfer resistance (R_ct), and improving the output, energy efficiency, and specific capacity of the zinc-air battery.
[0040] The CNT support is a carbon-based nanomaterial with excellent electrical conductivity and may be single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), or a mixture thereof. Since carbon nanotubes have a high aspect ratio and a large specific surface area, they provide a sufficient surface area for supporting catalytically active materials.
[0041] In addition, the CNT support forms a continuous electron transport path, thereby rapidly transferring electrons generated during the air electrode reaction, which reduces the internal resistance of the electrode and improves the output characteristics of the battery.
[0042] A polymer active layer containing an iron (Fe) macrocycle compound is formed on the surface of a carbon nanotube support and provides an active site where the actual oxygen reduction reaction (ORR) takes place.
[0043] Figure 1 is a schematic diagram illustrating the structural formula of a polymer containing an iron (Fe) macrocycle compound. Referring to Figure 1, the iron (Fe) macrocycle compound includes an iron-nitrogen (Fe-N4) bond structure that facilitates adsorption with oxygen molecules and charge transfer, thereby exhibiting strong catalytic activity that promotes oxygen reduction reactions. The iron (Fe) macrocycle compound includes an iron phthalocyanine (Fe-Phthalocyanine) or iron porphyrin (Fe-Porphyrin) structure, and the structure is connected in repeating units to form a π (pi)-conjugated polymer chain.
[0044] Iron macrocycle compounds possess a macrocycle structure containing iron (Fe) as the central metal and act as active sites that promote the adsorption and reduction of oxygen molecules. The iron center has an appropriate binding energy with oxygen, which stably induces the reaction pathway of the oxygen reduction reaction.
[0045] The iron macrocycle compound is contained within a polymer-type active layer, and the polymer structure stably anchors the iron center while simultaneously preventing the aggregation of catalytic active sites. Additionally, the polymer active layer enhances the bonding strength with the CNT support, thereby inhibiting the detachment or separation of the catalyst.
[0046] The monomeric form of the Fe macrocycle contains one Fe-N4 active site per molecule. In this structure, since each Fe-N4 active site exists separated at the molecular level, electronic interactions between active sites are limited.
[0047] In addition, monomer Fe macrocycles are mainly aggregated in the solid state in the form of π-π stacking or simple aggregation, in which case it is difficult to sufficiently form a continuous electron transport path penetrating the inside and outside of the aggregate.
[0048] The Fe-polymer active layer of the present invention has a π-conjugated polymer structure in which a plurality of Fe-N4 macrocycle units are repeatedly connected in the chain direction. That is, individual Fe macrocycles do not exist alone but are continuously arranged within chemically connected polymer chains. Accordingly, electron delocalization is possible along the lines between adjacent Fe-N4 units within the same polymer chain, and additional electron transfer pathways are formed between different polymer chains through π-π interactions and electron hopping. As a result, the entire polymer can function as a single continuous conductive network.
[0049] Figure 2 is a reference diagram to explain the effect that an air electrode catalyst coated with a polymer active layer containing an iron (Fe) macrocycle compound according to the present invention has superior electron conductivity and charge transfer resistance compared to an air electrode catalyst coated with a monomer active layer containing an iron (Fe) macrocycle compound. Figure 2 is a high-resolution XPS analysis result of Fe 2ps / ₂ to confirm changes in the electronic environment due to polymerization of the Fe-polymer catalyst.
[0050] In the case of the control Fe-monomer sample, the Fe 2p₃ / ₂ peak is located in the high binding energy region of approximately 711–712 eV. 3 The positive component is dominant, and Fe in the range of approximately 708–709 eV. 2 The positive component represents a relatively negligible area. This suggests that the iron central atom in the monomer state is relatively electron-deficient.
[0051] On the other hand, in the Fe-polymer sample of the present invention, Fe on the low bonding energy side 2 + A distinct increase in peak area is observed, and a tendency for the maximum value of the entire peak to shift toward lower binding energies is observed.
[0052] This downward shift in binding energy and Fe 2 The increase in the + component implies that electrons were delocalized along the π-conjugated chain during the polymerization process. Consequently, a higher electron density is formed at each Fe-N4 center, causing the iron central atom to Fe 3 + Fe in a governing state 2 It demonstrates that a transition to an electron-rich environment where + is dominant has occurred.
[0054] The Fe-polymer active layer of the present invention forms a continuous and uniform coating layer of a certain thickness along the CNT surface by bonding to the sp²-conjugated carbon framework of the CNT support through strong π-π interactions. This allows for the effective exposure of active sites with a higher density relative to the same mass, thereby significantly improving the actual utilization rate of active sites. Furthermore, the chemically immobilized polymer structure inhibits demetalation even under alkaline electrolyte conditions, providing excellent long-term structural stability.
[0055] The polymer active layer containing an iron (Fe) macrocycle compound formed on the CNT support in this way improves the activity of the oxygen reduction reaction (ORR) and the 4-electron (4e) path selectivity, and enables stable electrode performance even under high current density driving conditions.
[0056] FIG. 3 is a reference diagram for explaining a structure in which a polymer containing an iron (Fe) macrocycle compound is continuously coated on the surface of a CNT support. Referring to FIG. 3, the thickness of the polymer active layer containing the iron (Fe) macrocycle compound formed on the CNT support may be 0.5 nm. This ultrathin active layer prevents the active material from being excessively stacked and buried inside, and creates an environment in which a number of iron (Fe) active sites can come into direct contact with the electrolyte and oxygen.
[0057] Specifically, this utilizes the properties of iron (Fe) macrocycle compounds having a planar structure to maximize the exposure frequency of active sites by ensuring that molecules are evenly coated rather than stacked vertically. In other words, when the planar disc-shaped iron (Fe) macrocycle unit is formed with a thickness of 0.5 nm, which is equivalent to a monolayer, all active sites are exposed on the surface, maximizing the oxygen reduction reaction (ORR) efficiency. Consequently, as the distance electrons travel through the catalyst layer is minimized to the thickness of a single molecular layer, the charge transfer resistance (R) ct) is reduced and the output characteristics of the battery are improved. In addition, the active layer at the monolayer level is chemically and stably fixed to the surface of the CNT support through immobilization via strong π-π interactions with the CNT support, so that delamination or aggregation is effectively suppressed even during long-term operation.
[0058] According to another embodiment of the present invention, a method for manufacturing an air electrode catalyst for a zinc-air battery may include the steps of: preparing a carbon nanotube support; and supporting a polymer powder on the surface of the carbon nanotube support to form a polymer active layer containing the iron (Fe) macrocycle compound on the surface of the carbon nanotube support.
[0059] First, a conductive carbon nanotube (CNT) support is prepared. The carbon nanotubes may be single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), or a mixture thereof, and are suitable as catalyst supports due to their high electrical conductivity and large specific surface area. The CNT support acts as a core framework forming electron transport pathways in the air electrode catalyst and provides a foundation for the stable support of the subsequently formed polymer active layer.
[0060] Next, a polymer powder containing an iron (Fe) macrocycle compound is supported on the surface of a CNT support to form a polymer active layer on the surface of the CNT support.
[0061] At this stage, the polymer powder is the sp of the CNT 2 - By bonding through π-π interactions with the conjugated carbon skeleton, it can be formed as a continuous and uniform coating layer along the surface of the CNT. Accordingly, iron (Fe) macrocycle-based active sites are evenly distributed on the CNT support, thereby improving the practical utilization rate of active sites that contribute to the oxygen reduction reaction (ORR).
[0062] At this time, the polymer powder can be formed by mixing an iron precursor and a nitrogen-containing organic ligand, dissolving the mixed iron precursor and nitrogen-containing organic ligand in an organic solvent, centrifuging the dissolved solution mixed with the iron precursor and nitrogen-containing organic ligand, and drying the solution.
[0063] Specifically, first, an iron precursor and a nitrogen-containing organic ligand are prepared and mixed. The iron precursor subsequently acts as the central metal of the Fe-N4 macrocycle structure, and the nitrogen-containing organic ligand coordinates the iron center to form the macrocycle structure.
[0064] Subsequently, the mixed iron precursor and nitrogen-containing organic ligand are dissolved in an organic solvent to form a homogeneous solution. This step is intended to promote the reaction between the iron precursor and the ligand and to ensure the uniform formation of a macrocycle-based polymer structure.
[0065] Next, a dissolved solution containing a mixture of an iron precursor and a nitrogen-containing organic ligand is centrifuged and then dried to form a polymer powder. During this process, the solvent is removed, and a polymer powder in the form of a polymer containing an iron (Fe) macrocycle compound is obtained.
[0066] The polymer powder prepared in this way is subsequently supported on a CNT support to form a polymer active layer having a π-conjugated polymer structure.
[0067] Figure 3 is a reference diagram illustrating the structure in which a polymer containing an iron (Fe) macrocycle compound is continuously coated on the surface of a CNT support, and is the result of analyzing the microstructure of the polymer active layer formed on the surface of the CNT support using HAADF-STEM (High-Angle Annular Dark-Field Scanning Transmission Electron Microscopy). Referring to Figure 3, it can be confirmed that the polymer powder prepared according to the present embodiment is stably supported on the surface of the CNT support to form a continuous and uniform coating layer. In particular, since it is observed that the iron (Fe) signal is uniformly distributed across the entire area of the coating layer, it can be confirmed that highly dispersed Fe active sites have been successfully established on the CNT network through the process of the present invention.
[0068] In the polymer powder formation step according to the present invention, the reaction is carried out by mixing an iron precursor in a ratio of 20 to 30 weight% and a nitrogen-containing organic ligand in a ratio of 70 to 80 weight%. This compositional ratio is intended to sufficiently induce coordination bonding between the iron center and the nitrogen ligand so that a stable Fe-N4 macrocycle structure is formed.
[0069] If the content of the iron precursor is less than 20 wt%, the density of the formed Fe-N4 active sites is insufficient, which may reduce the catalytic activity required to induce an oxygen reduction reaction. Conversely, if it exceeds 30 wt%, the addition of an excessive iron species may cause particle aggregation or induce incomplete coordination with ligands, which may reduce the uniformity of the active sites; consequently, this causes a decrease in structural stability during long-term operation. Meanwhile, by maintaining the content of the nitrogen-containing organic ligand in the range of 70 to 80 wt%, the iron central atom is induced to be sufficiently and stably coordinated with nitrogen atoms. This suppresses the demetalation phenomenon, where the central metal detaches even in an alkaline electrolyte environment, thereby maximizing the lifespan characteristics of the catalyst.
[0070] Therefore, the mixing ratio of the iron precursor and the nitrogen-containing organic ligand specified in the present claim is an optimal range for simultaneously satisfying the formation of highly dispersed Fe active sites, the stable growth of the π-conjugated polymer structure, and securing electrical and chemical properties suitable for the oxygen reduction reaction (ORR).
[0071] At this time, as a raw material for forming a polymer active layer containing the iron (Fe) macrocycle compound, the iron precursor may include iron sulfate (FeSO₄), and the nitrogen-containing organic ligand may be 1,2,4,5-tetracyanobenzene (1,2,4,5-Tetracyanobenzene; TCNB). This combination of raw materials induces the stable formation of a π-conjugated polymer structure in which Fe-N4 active sites are repeatedly connected in the chain direction through a hydrothermal synthesis process.
[0072] Meanwhile, the step of forming a polymer active layer containing an iron (Fe) macrocycle compound comprises: a step of preparing a dispersion by dispersing polymer powder in a polar organic solvent; and a step of mixing and stirring carbon nanotube powder in the dispersion; wherein, the polymer powder and carbon nanotube powder may be mixed in a ratio of 15 to 20 weight% of the polymer powder and 80 to 85 weight% of the carbon nanotube powder based on the total weight thereof.
[0073] According to the present embodiment, a composite catalyst is prepared by dispersing polymer powder in an organic solvent and then mixing and stirring it with CNT powder. In particular, by limiting the content of the polymer powder to 15 to 20 weight percent of the total, a uniform coating layer with a thickness of about 0.5 nm is induced to form on the surface of the CNT support. If the polymer content is less than 15 weight percent, the number of effective active sites is insufficient, resulting in minimal performance improvement; if it exceeds 20 weight percent, the electron transfer efficiency may decrease due to excessive stacking of the catalyst layer. Therefore, through the above numerical range, stable output characteristics and high specific discharge capacitance can be secured even when driving at high current densities.
[0074] Meanwhile, according to another embodiment of the present invention, an air electrode of a zinc-air battery is disclosed, characterized by comprising: a carbon material including activated carbon and carbon black; a catalyst part including manganese dioxide (MnO2) and the air electrode catalyst described above; and a PTFE (Polytetrafluoroethylene) binder.
[0075] Since the air electrode catalyst according to this embodiment is identical to the air electrode catalyst of the zinc-air battery according to the preceding embodiment, the specific description will be replaced by the description of the preceding embodiment.
[0076] The air electrode for a zinc-air battery according to the present embodiment is manufactured by mixing a carbon material, a catalyst, and a binder in a certain ratio to ensure efficient oxygen reduction reaction (ORR) and smooth electron transfer.
[0077] At this time, the air electrode comprises, based on 100 weight% of the total, 70 to 80 weight% of activated carbon, 1 to 2 weight% of Black Pearl, and 0.5 to 1 weight% of Super P as carbon materials, 7 to 8 weight% of manganese dioxide (MnO2) as the main catalyst of the catalyst part, and 15 to 20 weight% of PTFE (Polytetrafluoroethylene) as a binder, and may include the air electrode catalyst according to claim 1 as an additive of the catalyst part in a ratio of 4 to 6 weight parts relative to 100 weight parts of manganese dioxide (MnO2).
[0078] Specifically, the carbon material includes activated carbon and carbon black, and serves to form electron conduction pathways within the electrode while facilitating the diffusion of oxygen gas and the discharge of reaction products. Activated carbon enables the effective dispersion and support of the catalyst through its high specific surface area and porous structure, while carbon black enhances the electrical conductivity of the entire electrode through its fine particle structure.
[0079] The carbon material may comprise 70 to 80 weight percent of activated carbon, 1 to 2 weight percent of Black Pearl, and 0.5 to 1 weight percent of Super P, based on 100 weight percent of the total. This composition is intended to simultaneously secure high conductivity and an appropriate pore structure, thereby reducing the internal resistance of the air electrode and enabling stable operation even under high current density conditions.
[0080] The catalyst section comprises manganese dioxide (MnO2) as the main catalyst and the aforementioned air electrode catalyst as the addition catalyst. Manganese dioxide (MnO2) is a material widely used as an ORR catalyst in the air electrode of zinc-air batteries, providing stable catalytic activity at a relatively low cost.
[0081] Meanwhile, in this embodiment, to compensate for the limitations of a manganese dioxide (MnO2) single catalyst, an air electrode catalyst comprising a polymer active layer containing an iron (Fe) macrocycle compound is introduced as an additive catalyst. Since the air electrode catalyst includes highly dispersed Fe-N4 active sites based on a CNT support, it contributes to improving the reaction rate of ORR and, in particular, increasing the 4-electron (4e) path selectivity.
[0082] At this time, MnO2 is included as the main catalyst of the catalyst section in an amount of 7 to 8 weight%, and the air electrode catalyst may be included in a ratio of 4 to 6 weight parts relative to 100 weight parts of MnO2. This ratio range corresponds to the optimal range for preventing catalyst aggregation or increased costs while maximizing the synergistic effect between the stability of MnO2 and the high activity of the Fe-based catalyst.
[0083] The binder is formed of PTFE (Polytetrafluoroethylene) and serves to bond the catalyst and carbon materials into an electrode form while simultaneously imparting hydrophobicity to the air electrode to inhibit electrolyte penetration. This allows the gas-liquid-solid three-phase interface to be stably maintained within the air electrode.
[0084] At this time, the PTFE binder may be included in an amount of 15 to 20 weight% based on 100 weight% of the total, which is a range to ensure a balance of mechanical strength and gas permeability of the electrode.
[0085] At this time, the air electrode catalyst may be included in a ratio of 5 parts by weight relative to 100 parts by weight of MnO2.
[0086] FIGS. 5 and 6 are reference diagrams for explaining the performance characteristics of a zinc-air battery according to the content of an air electrode catalyst coated with a polymer active layer containing an iron (Fe) macrocycle compound. FIGS. 5 and 6 relate to the results of comparing the discharge capacity (mAh / g) and potential holding characteristics under each catalyst condition (Fig. 5) and the results of comparing the discharge capacity (mAh / g) characteristics (Fig. 6), in the case where the air electrode catalyst is not included (Bare), in the case where a monomer active layer containing an iron (Fe) macrocycle compound is included in 5 wt% (Fe-Monomer@CNT, 5 wt%), in the case where a polymer active layer containing an iron (Fe) macrocycle compound is included in 2 wt% (Fe-Polymer@CNT, wt%), in the case where a polymer active layer containing an iron (Fe) macrocycle compound is included in 10 wt% (Fe-Polymer@CNT, 10 wt%), and in the case where a polymer active layer containing an iron (Fe) macrocycle compound is included in 5 wt% (Fe-Polymer@CNT, 5 wt%). This is a graph. In this case, when the polymer active layer containing an iron (Fe) macrocycle compound was included in 2 wt% by weight (Fe-Polymer@CNT, 2 wt%), when the polymer active layer containing an iron (Fe) macrocycle compound was included in 10 wt% by weight (Fe-Polymer@CNT, 10 wt%), and when the polymer active layer containing an iron (Fe) macrocycle compound was included in 5 wt% by weight (Fe-Polymer@CNT, 5 wt%), three cells were fabricated under the same conditions and repeated experiments were performed, and the results were superimposed and displayed on the graph.
[0087] This is intended to compare and analyze the discharge characteristics and reproducibility of zinc-air batteries according to changes in the amount of Fe-Polymer@CNT added.
[0088] As a result of comparing the discharge characteristics of zinc-air batteries with air electrodes, the electrode with a simple addition of Fe macrocycle monomers showed a limited improvement effect, with only a slight increase in discharge capacity compared to an air electrode composed solely of MnO2. On the other hand, when an Fe-Polymer@CNT catalyst was introduced in which Fe-macrocycle compounds are linked in a π-conjugated polymer structure and immobilized on a CNT support, it was confirmed that the discharge potential maintenance characteristics improved more distinctly along with an increase in discharge capacity. This can be interpreted as being due to the effective formation of electron transfer pathways in a structure combining polymerized Fe-polymer and a CNT conductive network, and the improved actual utilization rate of Fe-N4 active sites compared to the monomer.
[0089] On the other hand, when the amount of Fe-Polymer@CNT added was in the low content range (2 parts by weight), the density of conduction pathways and Fe-N4 active sites formed within the air electrode was insufficient; consequently, the improvement in discharge performance was limited, and performance variations between cells tended to be relatively large. This is attributed to the fact that the catalytic effect was not fully manifested due to an insufficient absolute number of Fe-based active sites.
[0090] Conversely, when Fe-Polymer@CNT was applied in a high content range (10 parts by weight), localized stacking or accumulation of the catalyst occurred within the air electrode, leading to cracking during electrode formation or partial blockage of gas and ion diffusion pathways. As a result, the shape of the discharge curve varied from cell to cell, and a tendency for increased variation in discharge capacity was observed.
[0091] In contrast, the air electrode with Fe-Polymer@CNT added in an intermediate content range (5 parts by weight) exhibited the most balanced performance in terms of discharge capacity, potential holding characteristics, and reproducibility between cells. When three or more cells were fabricated under the same conditions and repeated experiments were performed, it was confirmed that the discharge curves overlapped almost completely, which indicates excellent reproducibility between cells. Furthermore, in the comparison of specific capacitances shown in the bar graph, the intermediate content condition showed not only a high average value but also the smallest standard deviation (σ), suggesting excellent uniformity of electrochemical performance.
[0092] Table 1 below summarizes the results of comparing discharge capacity (mAh / g) characteristics according to Figure 6, and represents the average value calculated from multiple individual cell data repeatedly measured under each addition amount condition (Fe-Polymer@CNT, 2wt%, Fe-Polymer@CNT, 10wt%, Fe-Polymer@CNT, 5wt%). Table 1 supports the fact that the condition in which Fe-Polymer@CNT is applied at an intermediate content level (5 wt%) is the most desirable composition range in terms of performance and reproducibility.
[0093] Bare Fe-Polymer@CNT 5 wt% Fe-Polymer@CNT, 2wt% Fe-Polymer@CNT, 10wt% Fe-Polymer@CNT, 5wt% 용량 (mAh / g) 600 635 630 670 720
[0094] Accordingly, a composition containing 5 parts by weight of Fe-Polymer@CNT catalyst relative to 100 parts by weight of MnO2 is considered to be most suitable for the air electrode of a zinc-air battery.
[0095] Meanwhile, according to another embodiment of the present invention, a zinc-air battery is provided in which an air electrode catalyst comprising a polymer active layer containing the iron (Fe) macrocycle compound described above is applied to the air electrode.
[0096] The zinc-air battery according to the present embodiment may include a negative electrode containing zinc, an electrolyte, a separator, and an air electrode in which an oxygen reduction reaction occurs using oxygen from the air, and the air electrode catalyst described in the preceding embodiment is applied to the air electrode. The air electrode catalyst has a structure in which a polymer active layer containing an iron (Fe) macrocycle compound is formed on a carbon nanotube (CNT) support, and provides high electrical conductivity and excellent oxygen reduction (ORR) activity.
[0097] Since the composition, manufacturing method, and physical properties of the air electrode catalyst according to the present embodiment are substantially the same as those of the air electrode catalyst of a zinc-air battery described in the preceding embodiment, any redundant specific description thereof is replaced by the description of the preceding embodiment.
[0098] However, in the zinc-air battery of the present embodiment, the air electrode catalyst is applied within the air electrode, thereby uniformly expressing the catalytic reaction based on Fe-N4 active sites throughout the air electrode and stably forming an electron transfer pathway through the CNT support. Accordingly, the battery can exhibit improved potential retention characteristics and high discharge capacity during discharge, and can maintain stable performance even under repeated charge-discharge or long-term discharge conditions.
[0100] As such, according to the present invention, by coating a polymer active layer containing an iron (Fe) macrocycle compound on a carbon nanotube support, the electronic conductivity is improved and the charge transfer resistance (R_ct) is reduced, thereby having the effect of improving the output, energy efficiency, and specific capacity of a zinc-air battery.
[0101] In addition, it has the effect of enabling the precise coating of a polymer active layer containing an iron (Fe) macrocycle compound onto a carbon nanotube support with high density and high dispersion.
[0103] As described above, preferred embodiments according to the present invention have been examined. It is obvious to those skilled in the art that, in addition to the embodiments described above, the present invention may be embodied in other specific forms without departing from its spirit or scope. Therefore, the embodiments described above should be regarded as illustrative rather than restrictive, and accordingly, the present invention is not limited to the description above but may be modified within the scope of the appended claims and their equivalents.
Claims
Claim 1 A method for manufacturing an air electrode catalyst for a zinc-air battery, comprising: a conductive carbon nanotube (CNT) support; and a polymer active layer formed on the surface of the carbon nanotube support and containing an iron (Fe) macrocycle compound, the method comprising the step of preparing the carbon nanotube support; The method comprises the step of supporting a polymer powder on the surface of the carbon nanotube support to form a polymer active layer containing the iron (Fe) macrocycle compound on the surface of the carbon nanotube support; wherein the polymer powder is formed by mixing an iron precursor and a nitrogen-containing organic ligand, dissolving the mixed iron precursor and nitrogen-containing organic ligand in an organic solvent, centrifuging the dissolved solution containing the iron precursor and nitrogen-containing organic ligand, and drying the solution; wherein, when forming the polymer powder, the iron precursor and the nitrogen-containing organic ligand are mixed in a ratio of 20 to 30 weight% of the iron precursor and 70 to 80 weight% of the nitrogen-containing organic ligand based on their total weight; and the step of forming a polymer active layer containing the iron (Fe) macrocycle compound comprises the step of dispersing the polymer powder in a polar organic solvent to prepare a dispersion; and the step of mixing and stirring the carbon nanotube powder in the dispersion; wherein, the polymer powder and the carbon nanotube powder, their A method for manufacturing an air electrode catalyst for a zinc-air battery, characterized by mixing the polymer powder in a ratio of 15 to 20 weight% and the carbon nanotube powder in a ratio of 80 to 85 weight% based on the total weight. Claim 2 A method for manufacturing an air electrode catalyst for a zinc-air battery, characterized in that, in claim 1, the polymer active layer containing the iron (Fe) macrocycle compound is an iron precursor, and the nitrogen-containing organic ligand is TCNB. Claim 3 A zinc-air battery air electrode catalyst manufactured by the method for manufacturing an air electrode catalyst for a zinc-air battery according to claim 1. Claim 4 An air electrode catalyst for a zinc-air battery according to claim 3, wherein the iron (Fe) macrocycle compound comprises an iron phthalocyanine (Fe-Phthalocyanine) or iron porphyrin (Fe-Porphyrin) structure, and said structure is connected as repeating units to form a π-conjugated polymer chain. Claim 5 An air electrode catalyst for a zinc-air battery, characterized in that, in claim 4, the thickness of the polymer active layer containing the iron (Fe) macrocycle compound is 0.5 nm. Claim 6 A zinc-air battery comprising an air electrode catalyst according to paragraph 3. Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 delete Claim 11 delete
Citation Information
Patent Citations
Fabrication method of air electrode using α-phase manganese oxide / carbon nanotube composite, and the air electorde thereby
KR101197100B1
